Comparison of lipid profile between controlled and uncontrolled diabetic subjects (Bangladesh Journal of Pathology, 2010)
Keywords: Glycosylated hemoglobin; low-density lipoprotein cholesterol, type 2 diabetesDOI: 10.3329/bjpath.v25i1.4125Bangladesh J Pathol 25(1): 10-13